Featured Cover. Issue 3 (10th March 2022) - Chetan, Mayank; Sakib, M. Sadman; Griffith, D. Todd; Gupta, Abhineet; Rotea, Mario A.
Abstract : The cover image is based on the Research Article Design of a 3.4‐MW wind turbine with integrated plasma actuator-based load control by Mayank Chetan et al., https://doi.org/10.1002/we.2684 . Image courtesy of Arctura, Inc. and University of Texas at Dallas.